Evolution of the ecological security pattern of the Yellow River Basin based on ecosystem services: a case study of the Shanxi section, China - Wang, Jinfang; Lv, Zhihong; Zhen, Zhilei; Wu, Qian (Frontiers in Environmental Science, 2024)
Identifying and evaluating the ecological security pattern (ESP) of region can provide a solid foundation for optimizing regional ecosystem elements and improving regional ecological security. The PLUS model, InVEST model, and circuit theory were used to analyze the ecosystem services and ESP of the Shanxi section of the Yellow River Basin (SYRB) between 2005 and 2035. The findings revealed that (1) The total area of land use shift across categories between 2005 and 2020 was 6080.99 km2, or 5.22% of the SYRB's total area. Under the natural development scenario, the total land transfer area from 2020 to 2035 was predicted to be 4605.10 km2. Among these, the tendency for construction and forest land was expanding, while the tendency for cultivated land, grassland, water area, and unused land was shrinking; (2) From 2005 to 2035, the SYRB's water yield and soil conservation all decreased, while the habitat quality and carbon storage showed a declining tendency; (3) The ecological source increased from 35,767.00 km2 in 2005 to 39,931.00 km2 in 2035; the total length of the ecological corridors expanded from 2792.24 km to 3553.18 km between 2005 and 2035; the ecological pinch points increased from 27 in 2005 to 40 in 2035; the ecological barrier points increased from 21 in 2005 to 28 in 2035, which show that the ESP remained unstable; (4) According to the ecosystem service characteristics of the SYRB in 2020, an ESP of "one axis, two zones, four corridors, and multiple points" was constructed. This study could provide useful guidance for improving the spatial pattern of land use and maintaining ecosystem services.